Profiling the interaction mechanism of indole-based derivatives targeting the HIV-1 gp120 receptor1. Issue 95 (15th October 2015) - Wang, Jinghui; Li, Yan; Yang, Yinfeng; Zhang, Jingxiao; Du, Jian; Zhang, Shuwei; Yang, Ling
<x xml:space="preserve">Abstract</x> A glycoprotein exposed on a viral surface, human immunodeficiency virus type 1 (HIV-1) gp120 is essential for virus entry into cells as it plays a vital role in seeking out specific cell surface receptors for entry.